The Effect Of Chitin Synthesis Inhibitors (Csi) On Three Subterranean Termite Species (Blattodea: Rhinotermitidae, Termitidae) Towards The Termite Gut Symbionts - Shamsuri, Qurratu’Aini Syasya (2024)
The infestation subterranean termites were first encountered after establishment of rubber plantation during 20st century in peninsular of malaysia. Subsequently, interest has been devoted in termite research and chitin synthesis inhibitors (csi) has been introduced as one of numerous agents to against lower and higher termite infestation. Majority of published studies focused on efficacy and considering colony elimination in the absence of termites in the bait and monitoring station. However, there was dearth of studies assessing the impact on the feeding activity and mortality in laboratory bioassay, and the bait influence towards gut symbiont composition. Therefore, this study was performed on the lower (coptotermes gestroi) and higher termites (globitermes sulphureus and macrotermes gilvus), using three csi baits through ‘no-choice’ bioassay. Each of these baits also contained respective active ingredients which is widely used by pest companies in malaysia, and they are chlorfluazuron, bistrifluron, and hexaflumuron. The feeding activity was initially detected in c. Gestroi, followed by g. Sulphureus, and lastly m. Gilvus. The results determined that there were substantial differences (p < 0.05) in the feeding activity among the treated termites. However, unlike chlorfluazuron, only c. Gestroi was differed significantly from the other treated species. In response to all baits, m. Gilvus exhibited the highest mean mortality,